Pengaruh Kecemasan Matematika Terhadap Kemampuan Eksplorasi Matematis Pada Kelas XI - Isfahani Salsabilla; Dadang Rahman Munandar; Haerudin (Griya Journal of Mathematics Education and Application, 2025)
This study aims to examine the extent to which math anxiety affects mathematical exploration skills in students. This study uses a quantitative approach with the an ex post facto method and involves 52 students selected through purposive sampling. The research instruments consist of an essay test to measure mathematical exploratiom skills and a questionnaire to measure math anxiety. The data obtained were analyzed using simple linear regression with the assistance of IBM SPSS 25 for Windows Software. The analysis results showed that there wa a significant influence between math anxiety and mathematical exploration ability, with a coefficient of determination of 0,080. This means that math anxiety contributes 8% to mathematical exploration ability, while the remaining 92% is influenced by other factors outside the variables studied.